Face/core disbond fatigue growth in honeycomb cored aircraft sandwich elements under mixed mode flatwise tension loading. (January 2023) - Farshidi, Arash; Berggreen, Christian
Disbond damage growth in honeycomb cored sandwich structures due to static and fatigue mixed mode loading is investigated numerically and experimentally. A two dimensional finite element model was generated using core homogenization and the Crack Surface Displacement Extrapolation mode separation method, integrated into a fracture mechanics based analysis sub-routine to predict face/core interface fatigue crack propagation. The Cycle Jump technique was furthermore applied to accelerate fatigue analysis. Mixed mode fatigue characterization testing was conducted using Double Cantilever Beam specimens loaded with Uneven Bending Moments, generating a relationship between crack propagation rates and energy release rate amplitudes as a modified Paris Law, measured at three mode-mixity phase angles. The measured Paris laws were subsequently used as input data for the numerical fatigue model. The numerical model was validated against CFRP/Nomex ® Sandwich Tearing Test specimen tests with a propagating face/core interface crack yielding varying mode-mixities. The results from the validation showed good agreement between numerical predictions and experimental measurements.